MEDICAL PREVENTIVE MEASURES FOR LIVER CIRRHOSIS CAUSED BY HDV INFECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hepatitis D virus (HDV) infection remains a significant global health concern, especially due to its capacity to accelerate the progression of liver disease, including liver cirrhosis. Preventive measures play a crucial role in mitigating the burden of HDV-associated liver complications. This paper reviews the current medical preventive strategies aimed at reducing HDV infection rates and preventing liver cirrhosis progression in affected individuals. Key approaches include vaccination, antiviral therapies, lifestyle modifications, and early diagnosis.